2021
DOI: 10.1088/2053-1591/ac017e
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and selective deposition of carbon nanotubes from carbon nanoparticles mixture using mild acid treatment and electrokinetic manipulation

Abstract: Particle manipulation is often required in the fabrication of microelectronic devices such as transistors and sensors. In this work, we succeeded in depositing aligned carbon nanotubes (CNTs) from an oxidized conglomerates carbon mixture using a simple low power procedure consisting of mild acid treatment and frequency-dependent dielectrophoretic (DEP) force. The treatment improved the dispersity and solubility of CNTs due to the functional groups introduced on their surface. The DEP force was generated with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…The fourth sample was a mixture of MWCNTs and conductive amorphous carbon (CAC) functionalized with nitric acid, as described elsewhere. 40 One mg of each sample was added to 20 mL of dimethylformamide (DMF) at different concentrations. The solutions were sonicated for 30 minutes in a cold bath to form MWCNT suspensions.…”
Section: Methodsmentioning
confidence: 99%
“…The fourth sample was a mixture of MWCNTs and conductive amorphous carbon (CAC) functionalized with nitric acid, as described elsewhere. 40 One mg of each sample was added to 20 mL of dimethylformamide (DMF) at different concentrations. The solutions were sonicated for 30 minutes in a cold bath to form MWCNT suspensions.…”
Section: Methodsmentioning
confidence: 99%
“…Among the listed, the latter treatment is preferred since it is widely available, cost-effective, and requires much simpler installation. As the name implies, the wet chemical treatment utilizes wet chemicals, such as HCL [45], HNO 3 [46], H 2 O 2 [47], H 2 SO 4 [48], or a mixture of two or more acids to functionalize the tubes [49][50][51]. The harshness of the treatment is determined by several factors, including acid concentration, sonication time, treatment temperature, and oxidizing agents.…”
Section: Carbon Nanotube Treatmentsmentioning
confidence: 99%
“…Several million devices were packaged in a square centimeter [61]. Recent studies concluded that the quality of aligned CNTs using DEP depends on many factors, such as the electrode design [62,63], suspension quality [64], and CNTs enrichment [65,66].…”
Section: Alignment By Electric Forcesmentioning
confidence: 99%